Radiofrequency Radiation and Human Triiodothronine Hormone: Immunoenzymometric Assay - Fattahi-asl, Jafar; Karbalae, Mojtaba; Baradaran-Ghahfarokhi, Molood; Baradaran-Ghahfarokhi, Hamidreza; Khajoei-Fard, Rasha; Karbalae, Mitra; Baradaran-Ghahfarokhi, Milad (Recent Patents on Biomarkers, 2013)
The aim of this study was to investigate whether the thyroid Triiodothronine (T3) levels in the serum could be interfered by the exposure to the 900MHz cell phones in the laboratory. We also reviewed a selected number of recent patents relevant to the area of RF radiation and biomarkers. Human serum samples from 29 healthy donors were labeled with ruthenium to form a sandwich complex based on an immunoassay technique. All of them were placed into two batches, and the well heads in the first batch were exposed to 900MHz exposure emitted from a GSM mobile phone simulator for 18 min. Unexposed batch was served as the control sample under identical conditions and was compared with the exposed one in quantitative determination of T3 using the Wilcoxon test with criterion level of P = 0.050. Using the Wilcoxon test, there was no significant difference in serum T3 in the exposed group compared to the control group (P = 0.541). More accurate follow up studies are needed for the evaluation of the effects of the mobile phone use. The results here should be confirmed in the in vivo situation on mammalians and in larger series.
Keywords: immunoassay technique